Estratégias de manejo de irrigação para o cultivo da mangueira ‘Kent’ no Semiárido brasileiro - Andrade, Victor Pimenta Martins de (2021)
The production of mango (Mangifera indica L.) has great economic expression for Brazilian agriculture. The Northeast region accounts for about 77% of Brazilian production, with the largest producers being the states of Pernambuco and Bahia, which produced 518.2 and 442.2 tons, respectively. Of the 156 thousand tons of mangoes exported by the country, 84% of this quantity came from the São Francisco Valley, with the 'Kent' mango being one of the main cultivars produced in the region. Although mango is a drought-tolerant crop, inadequate irrigation management reduces productivity. However, some researches concluded that the reduction of the irrigation depth in less sensitive phenological stages may not harm or even improve fruit production and quality, with greater efficiency in the use of water. Thus, the objective was to evaluate physiological, productive, qualitative parameters and the economic viability of the 'Kent' mango tree when subjected to controlled water deficit in the phenological stages of flowering, fruit growth and fruit ripening. The experiment was conducted in an orchard at Fazenda Special Fruit, located in the municipality of Petrolina-PE, a semi-arid region of the Sub-middle of the São Francisco Valley. The climate of the region is classified, according to Köppen-Geiger, as BSw'h'. The experimental design used was randomized blocks, in a triple factorial scheme, with the application of four irrigation depths (40, 60, 80 and 100% of the crop evapotranspiration - ETc), three phenological stages (F1 - flowering, F2 - fruit growth, F3 - fruit ripening) and two consecutive production cycles (harvest of 2018 and 2019), with four replications, each plot consisting of four plants. During each phenological phase, the physiological parameters of gas exchange in the leaves were evaluated: photosynthesis, stomatal conductance, transpiration and leaf temperature. After harvesting, the production parameters were evaluated: number of fruits per plant, average fruit weight, productivity, water use efficiency and economic benefit/cost ratio; and qualitative: content of soluble solids, titratable acidity, pH, firmness and skin color. Irrigation with depths of 40% of ETc in the flowering phase and 80% of ETc in the fruit growing and ripening phase increased the number of fruits per plant, which resulted in increased productivity, efficiency in water use and benefit ratio/cost of growing the 'Kent' mango tree. Irrigation with a depth between 79.5 and 83.6% of ETc during the three phenological phases tested provided greater gas exchange, greater firmness and titratable acidity in the fruits. The reduction in the irrigation depth in the flowering and fruit ripening phases decreased the soluble solids content in the fruits, while in the fruit growing phase the highest soluble solids content was obtained with irrigation between 68.24 and 74.5% of ETc